Surface biological, chemical, and optical properties of the Patagonian Shelf coccolithophore bloom, the brightest waters of the Great Calcite Belt. (30th August 2014) - Balch, W. M.; Drapeau, D. T.; Bowler, B. C.; Lyczkowski, E. R.; Lubelczyk, L. C.; Painter, S. C.; Poulton, A. J.
Abstract : We report surface observations of a mesoscale coccolithophore bloom at the shelf break of the Patagonian Shelf during December 2008, representing the densest coccolithophore population in the Southern Ocean. The bloom was most intense within the Falklands Current, northeast of the Falkland Islands. Emiliania huxleyi dominated bloom waters, with a mixed E. huxleyi and Prorocentrum sp. dinoflagellate bloom to the west and mixed assemblage of diatoms, dinoflagellates, and flagellates to the east. Optical measurements of coccolith light scattering, analytical measurements of their calcite, and microscopic counts all showed this to be an intense coccolithophore bloom. Average particulate inorganic carbon per coccolith in the bloom was low, typical of the B coccolith morphotype and in agreement with independent measurements made by scanning electron microscopy. Highest particulate inorganic carbon (measured optically and chemically) was observed when residual nitrate (defined as the difference, [NO3 −1 ] − [Si(OH)4 ]) was 10–17 µmol L −1 and nitrate to phosphate ratios were close to Redfield values. Elevated particle backscattering was observed in the E. huxleyi bloom, whereas the highest particle scattering occurred in the adjoining Prorocentrum sp. bloom. Backscattering from coccolithophores represented up to 50% of the total backscattering (from organic and inorganic particles) along the main axis of the E. huxleyi bloom. Chlorophyll‐specific absorption in the coccolithophore bloom was typical of marine phytoplankton. Residual nitrate plotted vs. temperature showed that the E. huxleyi bloom was associated with waters between 5°C and 15°C, with depleted silicate. Results suggest that previous drawdown of silicate by diatoms occurred prior to the densest E. huxleyi blooms over the Patagonian Shelf. We speculate that such conditions might also be important for annual development of the broader Great Calcite Belt and other coccolithophore blooms..